2016
DOI: 10.1007/s00403-016-1618-y
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-C*06 allele as a possible genetic predisposing factor to psoriasis in South Indian Tamils

Abstract: Psoriasis is a multi-factorial heritable prototypical immune-mediated inflammatory disease, characterized by hyperproliferation of keratinocytes in the affected skin. There are no studies till date, to the best of our knowledge, about the association of HLA-C*06, the risk variant in the PSORS 1 susceptibility locus that confers the greatest risk for early onset of psoriasis, with the disease in South Indian Tamil patients with psoriasis. The present study was performed to determine the association of HLA-C*06 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…The worldwide HLA‐Cw6 allele frequency varies greatly and can range from 14·1% to 59·1%, whereas the percentage of patients with psoriasis carrying HLA‐Cw6 ranges from 10·5% to 77·2% (Table ) . Such wide ranges may be attributed to small sample sizes, ethnic diversity and differences in inclusion criteria.…”
Section: Hla‐cw6 Allele Frequency In Patients With Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…The worldwide HLA‐Cw6 allele frequency varies greatly and can range from 14·1% to 59·1%, whereas the percentage of patients with psoriasis carrying HLA‐Cw6 ranges from 10·5% to 77·2% (Table ) . Such wide ranges may be attributed to small sample sizes, ethnic diversity and differences in inclusion criteria.…”
Section: Hla‐cw6 Allele Frequency In Patients With Psoriasismentioning
confidence: 99%
“…They also have a significantly higher incidence of the Koebner phenomenon. In contrast, dystrophic nail changes and scalp involvement have been reported to be significantly less common in HLA‐Cw6 ‐positive patients . Interestingly, a recent meta‐analysis indicated that scalp lesions and nail psoriasis were associated with increased risk of developing PsA .…”
Section: Association With Disease Severitymentioning
confidence: 99%
“…[7] Our patient demonstrated typical appearance and location of BMG, though it may occur on other sites of oral mucosa than on the dorsum of the tongue where it is called geographic stomatitis. [7,8] BMG is usually asymptomatic. However, itching, foreign body sensation, mild pain and mild to severe burning sensation, which may occasionally interfere with eating or sleeping, have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient demonstrated typical appearance and location of BMG, though it may occur on other sites of oral mucosa than on the dorsum of the tongue where it is called geographic stomatitis [7,8]. BMG is usually asymptomatic.…”
Section: Discussionmentioning
confidence: 99%